Improvements in Activity and Stability of Immobilized Alcohol Dehydrogenase using Magnetic Carbon Nanotubes - Xiaosheng Tang (Science Faculty of Chiang Mai University, 2019)
Carbon nanotube (CNT) has been used for the immobilization of proteins and enzymes. However, the leakage of CNT into solution and difficulty in separation hindered the application of CNT. To minimize these shortcomings, CNT functionalized with magnetic particles was prepared and intended to be used in the immobilization of alcohol dehydrogenase (ADH) in this study. The obtained magnetic CNT (MCNT) was characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and vibration sample magnetometer (VSM). The operational stability was evaluated in repeated assay process, and the MCNT immobilized ADH (MCNT-ADH) retained 87.6 % of the initial activity after being used for 10 times. Compared with free ADH, MCNT-ADH exhibited improved pH and thermal stabilities. As a kind of novel immobilization support, MCNT could find considerable potential uses in industrial processes due to its better performance.